Indonesian theology students' foreign language reading anxiety and reading performance: A correlational study - Jeane Theresia Limeranto; Adaninggar Septi Subekti (Studies in English Language and Education, 2021)
This study investigated Theology students’ Foreign Language Reading Anxiety (FLRA) and the relationship between their FLRA and their reading achievement. A number of 63 Theology students participated in this quantitative study. A questionnaire developed by Saito et al. (1999) was used in obtaining the data for the study. The study was conducted to fill the void in the literature on the scarcity of empirical research on FLRA in the Indonesian English for Specific Purpose (ESP) context, especially among Theology students who were required to read a lot of English text and thus were very likely susceptible to experience reading anxiety. The study found that in general, the students experienced a medium level of FLRA. Low self-perceived reading competence and the unfamiliar topic of reading passages were reported to be attributed to higher FLRA levels whilst the formation of reading habits, reading exposure, and reading strategies were believed to reduce reading anxiety. This study further found a statistically significant negative correlation between the students’ FLRA and their reading achievement, albeit the strength being weak. This finding suggested that students’ FLRA could be a factor hampering learning. The present study’s specific finding on the possible positive impacts of reading strategies and the duration of reading exposure may indicate the urgency to incorporate these two aspects in the instructional design of English reading classes. Based on the findings, contributions, limitations, and suggested future studies were formulated.